Vectorial multipath channel estimation for the UTRA-TDD mode - Marques, P.
This paper, deals with channel estimation for UTRA-TDD. Based on the algorithm suggested by the 3GPP for scalar channels, a maximum likelihood (ML) approach for vectorial channel estimation, to include also the estimation of the direction-of-arrival, is proposed. The performance of the algorithm is assessed by resorting to simulations in typical UMTS scenarios, and also by comparing the RMS estimation errors against the Cramer-Rao bound. The results show that good performance is achievable from low to high values of Eb/N0, provided the path components are separated by more than 2 chips